2015
DOI: 10.1016/j.ces.2015.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Solution strategies to the stochastic design of mineral flotation plants

Abstract: The aim of this study is two-fold: first, to analyze the effect of stochastic uncertainty in the design of flotation circuits and second, to analyze different strategies for the solution of a two-stage stochastic problem applied to a copper flotation circuit. The paper begins by introducing a stochastic optimization problem whose aim is to find the best configuration of superstructure, equipment design and operational conditions, such as residence time and stream flows. Variability is considered in the copper … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…These studies have shown that the flotation circuit configuration is not very sensitive to stage recovery [9,19]. The overall output suggests that choosing the best flotation circuit is not sensitive to the stage recovery, and as a result, only approximate values of the recovery can be used to select the optimal flotation circuit [6,9,20]. This paper using simple numerical examples shows that the assumption of circuit configuration insensitivity to the stage recovery is not correct in all cases.…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations
“…These studies have shown that the flotation circuit configuration is not very sensitive to stage recovery [9,19]. The overall output suggests that choosing the best flotation circuit is not sensitive to the stage recovery, and as a result, only approximate values of the recovery can be used to select the optimal flotation circuit [6,9,20]. This paper using simple numerical examples shows that the assumption of circuit configuration insensitivity to the stage recovery is not correct in all cases.…”
Section: Introductionmentioning
confidence: 97%
“…This assumption may be very simplistic, but is commonly used in industrial operations [8]. Despite extensive researches had been done on the effect of design and operational parameters on the efficiency of flotation circuits, very few publications can be found in the literature that discusses the role of stage recovery on the overall circuit recovery and the effect of circuit configuration on the stage recovery [6,7,9,10]. Some previous studies have evaluated the circuit configuration with circuit analysis method assuming the same recovery in various flotation stages [7,11,12].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, several studies have been developed to evaluate the effects of uncertainties in flotation process design (Montenegro et al, 2013(Montenegro et al, , 2015Jamett et al, 2015;Cisternas et al, 2015). These studies have noted that the optimal flotation circuit structure is not very sensitive to the stage recovery values.…”
Section: Introductionmentioning
confidence: 98%